(untitled) (Texas Journal of Multidisciplinary Studies, 2026)
This article analyzes the role of geo-ideology as an ideological factor in the formation of a new world order. The study highlights the essence of the concept of geo-ideology, its interconnection with geopolitical and geo-economic processes, and its features of manifestation in the context of global transformations. Furthermore, the ideological foundations of the modern system of international relations are scientifically and theoretically substantiated through concepts such as geo-economics and geo-ideology. Globalization processes, inter-civilizational relations, and regional integration processes are analyzed as crucial factors in the formation of a new world order. The research results indicate that geo-ideology holds strategic importance in international politics.